Volières féminines - Julien Bondaz (Images Re-Vues)
The notion of the “human zoo”, which has met with great success, appears problematic for a number of reasons, starting with the indistinctness of the processes of animalization it proposes to bring together. However, the colonial period, which saw a proliferation of ethnographic exhibitions, also saw the development of analogies between women and birds. These analogies were all the more numerous as they referred to very concrete practices of using feathers in fashion and music hall, and the construction of colonial aviaries (displaying birds from the colonies). The feather trade and the broader success of exotic birds were also linked to colonial expansion. At the time, the metaphor of the aviary was widely used in connection with “exotic dances”. The gendered construction of this ornithological imaginary can be observed in colonial exhibitions and the colonial sections of universal exhibitions, as well as in fashion and music hall. By examining the reasons and motives for this, and by describing concrete cases in which encounters between exotic birds and the female body were portrayed, including spectacular encounters (such as that of Josephine Baker), this article aims to highlight the cross-cutting nature of these processes of ‘ornithologisation’, at the intersection between colonial domination and gender relations.